2015
DOI: 10.3329/ptcb.v25i1.24123
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Transformation of Plumbago zeylanica with Agrobacterium rhizogenes Strain LBA 9402 and Characterization of Transformed Root Lines

Abstract: High frequency transformation (73.80 ± 2.24%) has been obtained in Plumbago zeylanica using nodes and internodes of axenic whole plants infected with Agrobacterium rhizogenes strain LBA 9402. The root lines could be distinguished morphologically into two types : Root lines of morphotypes I and II. While morphotype I showed profuse branching with short (< 1 cm), highly dense hairy laterals, the roots of morphotype II roots were characterized also by profuse branching with long hairy laterals (> 3 -4 cm). Only f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The CDSs of BrrICE1.1 and BrrADC2.2 and their reverse complementary sequences were cloned into PRI101-AN-Flag vectors. Then, these constructs were separately transferred into A. rhizogenes LBA9402 by electroporation [ 47 ]. Cotyledon infection was used to transform the above genes into turnip roots, and the gene expression levels and putrescine content in the hair roots were extracted and analyzed by qRT-PCR and LC-MS, respectively, as described above.…”
Section: Methodsmentioning
confidence: 99%
“…The CDSs of BrrICE1.1 and BrrADC2.2 and their reverse complementary sequences were cloned into PRI101-AN-Flag vectors. Then, these constructs were separately transferred into A. rhizogenes LBA9402 by electroporation [ 47 ]. Cotyledon infection was used to transform the above genes into turnip roots, and the gene expression levels and putrescine content in the hair roots were extracted and analyzed by qRT-PCR and LC-MS, respectively, as described above.…”
Section: Methodsmentioning
confidence: 99%
“…This is due to the high density of bacteria that can damage cells or plant tissue. Basu et al (2015) study on Plumbago zeilanica reported that the OD 600 ˃ 0.1 is best density of Agobacterium rhizogenes strain LBA 9402.…”
Section: Resultsmentioning
confidence: 99%
“…There are contradictory reports regarding the extent of stability in transformed roots maintained in vitro during prolonged culture. Stability in growth and morphological characters over prolonged culture is reported in different species like Lycopersicon esculentum [518], Cinchona officinalis "Ledgeriana" [519], Aesculus hippocastanum [520], Pimpinella anisum [521], Plumbago zeylanica [522], Rauvolfia serpentina [522], Tylophora indica [523], Bacopa monnieri [524], etc. However, instability in morphological phenotype and growth kinetics of hairy roots in prolonged in vitro culture is reported in certain species like carrot, Brugmansia candida, Duboisia myoporoides, Hyoscyamus muticus, etc.…”
Section: Hairy Root Culturesmentioning
confidence: 99%